The effect of dedicated breast surgeons on outcomes in breast cancer: do numbers matter? - Clare, S. E. (Senologie - Zeitschrift für Mammadiagnostik und -therapie, 2015)
Improved clinical outcomes as a function of larger case volume likely reflects both the technical competence of the surgeon and his/her participation in a multidisciplinary care team. Increased case numbers are associated with larger percentages of margin-free excisions, smaller volumes of resection and decreased surgical complications for patients undergoing skin-sparing mastectomy with preservation of the nipple-areolar complex. Increased case numbers are also associated with the patient’s receipt of radiotherapy and systemic therapy.
Keywords: breast cancer; case numbers; margins; recurrence; survival; sentinel lymph node; cosmesis; skin-sparring mastectomy; multidisciplinary